Acaricidal and Insect Antifeedant Effects of Essential Oils From Selected Aromatic Plants and Their Main Components - Valcárcel, Félix; Olmeda, A. Sonia; González, Marta G.; Andrés, Maria Fe; Navarro-Rocha, Juliana; González-Coloma, Azucena (Frontiers in Agronomy, 2021)
This work has demonstrated the ixodicidal and insect antifeedant effects of essential oils from 14 experimentally cultivated aromatic plants. The strong ixodicidal and antifeedant oils corresponded to Thymus zygis, Thymus vulgaris, Satureja montana, Oreganum virens and Mentha suaveolens. The moderately active oils were from Lavandula angustifolia, Mentha piperita, Mentha spicata, Artemisa herba-alba and Rosmarinus officinalis. The most effective larvicidal and antifeedant compounds were piperitenone oxide, carvacrol, piperitenone and thymol, explaining the effects of the most active essential oils. The rest of tested compounds were not ixodicidal or antifeedant. Therefore, the activity of moderately active oils cannot be explained by their main components (linalyl acetate, linalool, menthone, menthol, limonene, camphor, 1,8-cineole, p-cymene, α-pìnene, carvone) suggesting synergistic effects. Considering the ixodicidal and antifeedant effects of these extracts, the plants have been ranked in relation to Thymus vulgare, a commercial biopesticide ingredient, for their potential as botanical pesticides. T. zygis, S. montana, and M. suaveolens ranked over T. vulgaris as ixodicidal agents and S. montana as insecticidal. Therefore, we propose the plant populations of S. montana, T. zygis and M. suaveolens tested here for further development as biopesticide ingredients.